The Legionella pneumophila effector LpdA is a palmitoylated phospholipase D virulence factor - Schroeder,GN; Frankel,G; Tate,EW; Aurass,P; Oates,CV; Hartland,EL; Flieger,A (Infection and Immunity, 2015)
Legionella pneumophila is a bacterial pathogen that thrives in alveolar macrophages, causing a severe pneumonia. The virulence of L. pneumophila depends on its Dot/Icm type IV secretion system (T4SS), which delivers more than 300 effector proteins into the host, where they rewire cellular signaling to establish a replication-permissive niche, the Legionella-containing vacuole (LCV). Biogenesis of the LCV requires substantial redirection of vesicle trafficking and remodeling of intracellular membranes. In order to achieve this, several T4SS effectors target regulators of membrane trafficking, while others resemble lipases. Here, we characterized LpdA, a phospholipase D effector, which was previously proposed to modulate the lipid composition of the LCV. We found that ectopically expressed LpdA was targeted to the plasma membrane and Rab4- and Rab14-containing vesicles. Subcellular targeting of LpdA required a C-terminal motif, which is posttranslationally modified by S-palmitoylation. Substrate specificity assays showed that LpdA hydrolyzed phosphatidylinositol, -inositol-3- and -4-phosphate, and phosphatidylglycerol to phosphatidic acid (PA) in vitro. In HeLa cells, LpdA generated PA at vesicles and the plasma membrane. Imaging of different phosphatidylinositol phosphate (PIP) and organelle markers revealed that while LpdA did not impact on membrane association of various PIP probes, it triggered fragmentation of the Golgi apparatus. Importantly, although LpdA is translocated inefficiently into cultured cells, an L. pneumophila ΔlpdA mutant displayed reduced replication in murine lungs, suggesting that it is a virulence factor contributing to L. pneumophila infection in vivo.